Improvement of Quality Characteristics and Shelf Life Extension of Raw Chicken Meat by Using Black Mulberry Leaf (Morus nigra L.) Extracts - Yasemin Çelebi̇ (Journal of Food Quality)
The objective of this study was to examine the impact of different concentrations of black mulberry leaf extract (BMLE) on the microbial quality, lipid oxidation, biogenic amine content, color stability, and sensory attributes of raw chicken meat during a 12-day chilled storage period. The raw chicken meat was treated with 0.1% BHT (positive control), 0.1%, 0.3%, and 0.5% BMLE, and the outcomes were then compared to the results obtained from raw chicken meat with no additive (control). In comparison to the control group, the inclusion of BMLE resulted in a decrease (P<0.05) in pH and thiobarbituric acid reactive substances (TBARS), as well as an improvement in redness (a∗) (P<0.05). The addition of BMLE significantly extended the shelf life of raw chicken meats compared to the control, as it limited microbiological development and lipid oxidation during storage (P<0.05). Additionally, the BMLE exhibited the most potent inhibitory impact on the buildup of these four BAs (tyramine, cadaverine, histamine, and tyramine) in raw chicken samples at the 12-day storage period (P<0.05). Despite the 0.5% BMLE groups’ lowest results for microbial counts, TBARS, and biogenic amines, the concentration of 0.3% BMLE proved to be the most advantageous in terms of sensory acceptability. These findings suggested that BMLE, rather than artificial chemicals, could be utilized in raw chicken products as a promising natural antioxidant and antibacterial agent.